KEKAYAAN DAN KERAGAMAN LINGUISTIK NUSANTARA, SEBUAH IDENTITAS WARISAN BUDAYA YANG TERABAIKAN DAN TERANCAM PUNAH (Sebuah Tinjauan Aspek Sosiolinguistik dan Pragmatis Pelestarian Bahasa Berbasis Komunitas) - Lambe, Petrus (Jurnal Insani, 2018)
If you talk to man in a language he understands-that goes to his head. If you talk to him in his own language- that goes to his heart”, (Nelson Mandela). This statement confirms that the choice of language in communicating with someone really determines whether the message to be conveyed can be fully understood or not. Bahasa Daerah (BD) as an inherited language which is actively used in the family or becomes a mother tongue is identified able to provide a complete understanding and even touch of feelings.Indonesia is home to 719 languages and is the second richest country with its language after Papua New Guinea (PNG) with over 800 languages (Ethnologue edition 21, 2018). Bahasa Indonesia (BI) is the most dominant language used in all regions of Indonesia today, because its function is the official language of the state and the language of unity. The contacts of BD-BI and BA (Bahasa Asing) will naturally conditioned BD in an increasingly weak position, especially in BD minorities and have gradually lost their function, even left by their speakers. The loss of language means losing all the knowledge and local wisdom inherent in it and documentation through writing, audio and visualization certainly cannot represent the natural conditions.Community-based language development where the communities actively involved in the entire process of identification, decision making and planning fosters responsibility and a sense of belonging to their local language and culture. Policy support from the local government is needed to legitimize and protect the richness of local languages and cultures in a sustainable manner, as mandated by the UUD 1945, specifically Chapter XV Article 36, that; (1) BD is maintained by the speaker, (2) will be respected and maintained by the State, and (3) as part of Indonesian culture (Sutama, 2011).